Analisis Life Cycle Assessment Produksi Biokoagulan Cangkang Maggot - Marshanda Afifa Shalsabila; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Black soldier fly shell as biocoagulant is considered effective in removing pollutants, making it a potential alternative coagulant in the coagulation-flocculation process. However, studies on the environmental impact of natural coagulant production need to be conducted as an assessment of the sustainability of natural coagulants. This study aims to analyze the environmental impacts caused by the production of black soldier fly shell biocoagulant using Life Cycle Assessment (LCA) with the ReCiPe 2016 method through Midpoint and Endpoint approaches using the SimaPro 9.6.0.1 software. The Life Cycle Assessment (LCA) was conducted with a gate-to-gate system boundary and a functional unit of 0.1 kg of raw biocoagulant material. Based on the results, the Midpoint approach showed the largest impact category as human carcinogenic toxicity with a total score of 1.07. Additionally, the Endpoint approach identified the largest impact category as human health with a total score of 20.7 Pt. The biggest contributor to the environmental impact in the production of black soldier fly shell biocoagulant is the chitosan dissolution stage, amounting to 5.11 Pt from the total human health impact. This is caused by electricity use, which affects human health.